(untitled) (Reflection and Critique Law Magazine, 2020)
The present study addresses animal protection under the terms set forth by the Brazilian Civil Code that classifies them as moving, specifically in the chapter governing movable property. An empirical analysis is performed, confronting the homeland norm with foreign norms where there is a mismatch, even a certain delay in the way the theme is approached in the Brazilian legal system. The survey scrutinizes Senate Bill No. 351 of 2015, which emphasizes the urgency of modifying animal protection, given that such non-human beings are, according to various scientific indications, sentient beings, capable of reasoning and feelings. This study is also justified by the changes in the relationship between humans and animals, where animals are no longer treated as property, but members of a family nucleus, as will be shown by the precedent jurisprudence in decisions handed down by the Superior Court of Justice. It is important to stimulate the debate about the transformation of the conceptualization of animals by the national civil law, in order to verify its leveling with the global understanding that animals are treated not as an object of law but as a subject of rights, tutelage. By laws designed to regulate the preservation of their right to life and protection against abuse.